Glutathione S-Transferases in Pediatric Cancer - Luo, Wen; Kinsey, Michelle; Schiffman, Joshua D.; Lessnick, Stephen L. (Frontiers in Oncology, 2011)
The glutathione S-transferases (GSTs) are a family of ubiquitously-expressed polymorphic enzymes important for detoxifying endogenous and exogenous compounds. In addition to their classic activity of detoxification by conjugation of compounds with glutathione, many other functions are now found to be associated with GSTs. The associations between GST polymorphisms/functions and human disease susceptibility or treatment outcome, mostly in adults, have been extensively studied and reviewed. This mini review focuses on studies related to GST epidemiology and functions related to pediatric cancer. Opportunities to exploit GST in pediatric cancer therapy are also discussed.